Chemical Composition and Digestibility of Major Feed Resources in Tanqua-Abergelle District of Central Tigray, Northern Ethiopia - Tikabo Gebremariam; Shumuye Belay (The Scientific World Journal)
Background. A detailed study on the feed quantity and quality is required to document the available feeds and their nutritional values. Aim. The study was aimed to investigate and document the chemical composition and in vitro dry matter digestibility of major feed resources available in Tanqua-Abergelle district of central Tigray, northern Ethiopia. Methods. Ten different feed resources were evaluated for their nutritive values. Representative feed samples were collected and prepared following appropriate procedures. The samples were subjected to analysis of chemical composition and in vitro dry matter digestibility (IVDMD) using proper scientific procedures. Results. Wide variations were observed in nutritive values of the investigated feeds. The highest crude protein (CP) was measured in Atella (15.90%) followed by green grass (13.20%), mill waste (10.90%), groundnut straw (9.18%), and cowpea straw (8.11%) in descending order. Mill waste (11.84 MJ/kg DM) and Atella (11.81 MJ/kg DM) had the highest metabolizable energy (ME) followed by green grass (9.83 MJ/kg DM), groundnut straw (9.28 MJ/kg DM), Teff straw (8.56 MJ/kg DM), and cowpea straw (8.39 MJ/kg DM) in that order. The highest NDF was recorded in groundnut null (79.80%) and the lowest NDF in mill waste (35.00%) and Atella (40.60%). The highest IVDMD was seen in mill waste (81.43%) and Atella (81.21%) and the lowest in groundnut hull (39.95%). Conclusion. The nonconventional feeds have moderate protein and reduced fiber contents, and thus, they can be utilized as supplement for poor-quality feeds. These feeds need further investigation using animals to substantiate the current study.